David Hodges Embarks on N'we Jinan Community Tour - Quebec Community Groups Network (QCGN) (2014)

2013-2014 Annual Report - Cote des Neiges Black Community Association (CDNBCA) (2014)
Striving for excellence since 1972, our organization’s vision and mission is focused on helping Black Canadian families rise above structural inequalities and systemic discrimination. Through our programs and services now more than ever before, we are ready to reaffirm and remember the contribution of Montreal’s Black communities to this society and celebrate our identity and heritage. It is time to allow our unique strengths to become louder than our weaknesses and take strategic steps towards better and sustainable futures. It is time to take care of ourselves, support each other and empower our community to overcome the forces that impede individuals to gain fair access to resources and opportunities. Together we can rewrite our legacy.